The Subway Grate Scene in The Seven Year Itch: “The Staging of an Appearance-As-Disappearance” - Smith, Graham (Cinémas)

(untitled) (Cinémas, 2004)
AbstractThe subway grate scene in The Seven Year Itch is placed in context, creating a “montage of attractions” that illuminates the iconic images of Marilyn Monroe. Parallels in earlier films situate these images in cinematic history, while later references to them demonstrate their continuing modernity. The “wondrous revealment” of women’s undergarments is also a common theme in literature. Freud’s writings on sexuality explain this preoccupation, while Barthes’s focus upon the erotic character of “intermittence” points to fundamental differences between “appearance-as-disappearance” in cinema and literature and the treatment of similar subjects by still photographers.